2013
DOI: 10.1016/j.neuron.2013.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase and Polyamination of Tubulin: Posttranslational Modification for Stabilizing Axonal Microtubules

Abstract: SUMMARY Neuronal microtubules support intracellular transport, facilitate axon growth, and form a basis for neuronal morphology. While microtubules in non-neuronal cells are depolymerized by cold, Ca2+ or antimitotic drugs, neuronal microtubules are unusually stable. Such stability is important for normal axon growth and maintenance, while hyperstability may compromise neuronal function in aging and degeneration. Though mechanisms for stability were unclear, studies suggested that stable microtubules contain b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
200
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(206 citation statements)
references
References 53 publications
6
200
0
Order By: Relevance
“…Tubulin posttranslational modifications are chemically diverse, ranging from phosphorylation (17), acetylation (18,19), palmitoylation (20), sumoylation (21), polyamination (22), and S-nitrosylation (23) to tyrosination (24), glutamylation (25,26), and glycylation (27). Most of these modifications are reversible.…”
mentioning
confidence: 99%
“…Tubulin posttranslational modifications are chemically diverse, ranging from phosphorylation (17), acetylation (18,19), palmitoylation (20), sumoylation (21), polyamination (22), and S-nitrosylation (23) to tyrosination (24), glutamylation (25,26), and glycylation (27). Most of these modifications are reversible.…”
mentioning
confidence: 99%
“…It has been demonstrated that axonal MTs are more resistant to the MT depolymerizing drug nocodazole compared to the dendritic MT population (Baas et al 1991;Witte et al 2008). Recently, a new posttranslational modification of tubulin has been identified that directly confers stability to MTs (Song et al 2013). Biochemical characterization of stable MT fractions demonstrated that polyamination of tubulin is directly involved in stabilizing neuronal MTs.…”
Section: Organization Of Axonal and Dendritic Microtubulesmentioning
confidence: 99%
“…If there is no primary amine present, water may act as the attacking nucleophile, resulting in the deamidation of glutaminyl residues to glutamyl residues, ( Figure 1, example 3). Regarding the physiological roles played by the transglutaminase activity, recently transglutaminase-catalyzed polyamination of tubulin has been shown to stabilize axonal microtubules, suggesting an important role for these reactions also during some physiological processes, such as neurite outgrowth and axon maturation [4] . The reactions catalyzed by TGs occur with little change in free energy and hence should theoretically be reversible.…”
Section: Tgmentioning
confidence: 99%